Ethics Dumping: Case Studies from North-South Research Collaborations - Schroeder, Doris; Cook, Julie; Hirsch, François; Fenet, Solveig; Muthuswamy, Vasantha (SpringerBriefs in Research and Innovation Governance, 2018)
Global Research Ethics; Global Bioethics; North-South Collaborations; Exploitation Vulnerability; Research Governance; Double Standards in Research; Ethics Dumping Examples